Dostępność rodziców w dzieciństwie a przywiązanie do partnera w związku intymnym - Alabrudzińska, Adamina; Bakiera, Lucyna (Człowiek i Społeczeństwo, 2021)
The presented research aimed to check how, depending on different experiences in the relationship with parents during childhood, young adults function in an intimate relationship. The style of attachment to a partner was the key research category. For this purpose, the Plopa Questionnaire of Attachment Styles and survey questions were used, which allowed estimating the total index of parents’ availability. 71 people (female 50,7%) in early adulthood participated in the study. Data collection was carried out in direct contact. The results showed that a higher level of accessibility of both parents in childhood coexists with a greater intensity of the secure style of attachment to a partner in an intimate relationship. The level of parents’ availability in childhood does not correlate with unsecured styles of attachment to a partner, both among adults coming from postdivorce and full families.